Analysis of T cell subsets in lichen planus- a perception to pathogenesis - Sangeetha, R. Shubha; Singh Thakur, Anamika; Manjunatha, Y.A. (Tropical Journal of Pathology and Microbiology, 2019)
Introduction: Lichen planus (LP) is a chronic inflammatory dermatosis, histopathologically characterized by band like lymphohistiocytic infiltrate obscuring the dermo-epidermal interface and associated with basal cell vacuolar degeneration. Cell mediated cytotoxicity as evidenced by dermal T lymphocytes have been postulated to initiate or stimulate the pathogenic mechanisms for Lichenoid dermatitis. Aims and Objective: The aim of the study is 1) To determine the T cell subsets in the inflammatory population. 2) To analyze the pattern of distribution of T cells subsets in histopathologically diagnosed cases of LP. Materials and Method: Biopsies received from Dermatology department of Dr B R Ambedkar Medical College and histopathologically diagnosed as LP were subjected for immunohistochemistry for CD4 and CD8.Manual quantification and distribution of T cell subsets were analyzed by 2 individual observers. Result: Forty cases of LP diagnosed histopathologically were subjected for immunohistochemistry for CD4 and CD8. The mean age of the patients were 35.74 years with slight female predominance (F:M ratio 1.5:1). A mixed CD4 and CD8 phenotypes were identified in inflammatory population. At the dermo-epidermal junction the mean CD8+ T cells subset was 67.5± 9.92 % and mean CD4+ T cells was 32.5±9.92 %. Perivascular quantification revealed a mean CD4+ T cells of 55±10.82 %and mean CD8+ T cells of 45±10.82%. Conclusion: In LP cases as CD8+ cytotoxic T cells density was more in D-E Junction compared to CD4+ T helper cells, a pathogenetic role of CD8+ T cells can be highlighted in basement membrane damage. An increase in perivascular CD 4+ T cells concentration signifies the pathogenetic role of dual T cell subsets in LP. This study would perhaps give a better insight to dermatologist to improvise the treatment response.